Color as a tool for quantitative analysis of heterogeneous polymer degradation. (April 2023) - Spencer, M.; Fuchs, W.; Ni, Y.; Li, D.; Pallaka, M.R.; Arteaga, A.; Fifield, L.S.
Abstract: Despite the fact that polymers are widely used in both our homes and industrial applications, critical insights into their degradation mechanisms when exposed to harsh environmental conditions, such as elevated temperature or radiation, are lacking quantifiable metrics. In oxygenated environments, polymer degradation is dominated by thermal-oxidation or photo-oxidation and in many cases occurs in a heterogeneous fashion throughout the thickness. While the heterogeneous oxidation of polymers is a common phenomenon, the effect on the functional lifetime of polymers is not well understood. Methods to evaluate such oxidation phenomena are time consuming and a challenge to implement. Here we show a novel approach for a quantitative evaluation of heterogeneous oxidation in polymers, using a fast and accurate color measurement technique. The proposed color analysis approach was observed to improve the efficiency of obtaining heterogenous oxidation profiles in half the time of common approaches, such as indention or Fourier transform infrared spectroscopy. Furthermore, the method was verified by mapping oxygen concentration through sample thickness using energy dispersive X-ray spectroscopy. The utility of the proposed method is demonstrated through the generation of an oxidation framework, aimed at an intelligent design of experiments for polymer lifetime prediction. We anticipate this work to be a starting point for further evaluation of heterogeneous oxidation in polymers using optical properties. Graphical abstract: Image 1 Highlights: Color enables fast and direct visualization of the heterogeneous oxidation of polymers. Total color difference correlates with Fourier transform infrared, nanoindentation, and scanning electron microscope energy dispersive X-ray spectroscopy testing. Oxidation framework developed towards the intelligent design of accelerated aging.